Smart city based on community empowerment, social capital, and public trust in urban areas - H. Herdiansyah (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Urbanization has been causing many problems for the environment and society. An ineffective and inefficient government also contributes to urban problems by increasing public dissatisfaction and distrust of government. Technological Improvements makes it possible for local governments in Indonesia to implement the concept of  “Smart City” as a solution to solve urban problems. This study aims to fill the gap by examining the impact of smart city application on public trust towards the government.METHODS: A primary data collection was conducted in 2021 to profile the citizens' behaviour in terms of smart city application. This study had surveyed four big cities in Indonesia that had built smart city applications well: Jakarta, Bandung, Semarang, and Surabaya. The primary data were analyzed through ordinary least squares regression.FINDINGS: This study founds that the fundamental factors of smart city applications that are statistically significant were on quality, satisfaction, and reliability. These factors had positive and significant impacts on the level of trust in the local government. Based on the regression model, the increase of application quality score by 1 affects the score of trust in the local government, which will rise by 0.440 (Jakarta), 0.269 (Bandung), and 0.245 (Semarang), and 0.212 (Surabaya). The increase in application satisfaction score by 1 affects the score of trust in local government, which will rise by 0.193 (Jakarta), 0.431 (Bandung), 0.07 (Semarang), and 0.186 (Surabaya). Also, an increase in application reliability score by 1 affects a rise in trust in local government by 0.187 (Jakarta), 0.204 (Bandung), 0.137 (Semarang), and 0.192 (Surabaya).CONCLUSION: Smart city applications can shape public trust by increasing the application's quality, satisfaction, reliability and community empowerment. However, it should be noted that the number of community which uses smart city application is still low. Therefore, It is necessary to encourage a culture of using those applications to help build citizens’ trust in the government and improve urban quality.